Football league for mobile using android application technology - Muhammad Afiq, Azmi (2013)
Modern hand held devices such as smart phones and PDAs have become increasingly powerful in recent years. Dramatic breakthroughs in processing power along with the number of extra features included in these devices have opened the doors to a wide range of commercial possibilities. As mobile devices become more like PCs they will come to replace the source of entertainments. One of popular entertainment is football. In Malaysia, there is Malaysia Super League (MSL), which it is lack of popularity as it needs a medium to increase popularity of the league. One of the contributing factors is provide medium for people to access the information regarding MSL. In order to resolve this problem, an application will be developed for user to get information about MSL.